Exploring Generalized Anxiety Disorder in Third-Year Medical Students: A Cross-Sectional Study Investigating Treatment-Seeking Attitudes - Mansoor, Noman; Warsi, Aimen; Khan, Mahnoor (European Scientific Journal, ESJ, 2023)
Objective: This study analyzes the levels and rates of generalized anxiety among third-year medical students and what prevents them from seeking treatment. It is an observational, prospective, cross-sectional study conducted among the students of third-year MBBS studying at Karachi Medical and Dental College. The questionnaire, which consisted of 17 questions, was sent out online among all the 254 students studying in their third year in college. The response rate was 35%. The responses were collected, evaluated, and analyzed using IBM SPSS 22 software (presented using counts and percentages). Results: Our study showed that 36% of students were facing mild, 25.1% of students were facing moderate and 36% of the students were facing a severe form of generalized anxiety. When it comes to what prevents them from seeking treatment for their condition, 10(5.2%) have no access to a psychiatrist, 16(8.3%) feel shy sharing their problem with the doctor and 4(2.1%) feel like there is no solution to their condition. 14(7.3%) cannot afford treatment, and 12(6.3%) do not want people, relatives, or parents to know that they seek treatment for anxiety. 38(19.8) feel like they can deal with it on their own, 23(12%) feel like it will get better on their own whereas 16(8.3%) are very busy because of medical college and do not have time to seek treatment. 12(6.3%) do not have the energy, 29(15.1%) feel like it is just a phase, and they will get through it and 18(9.4%) feel like they do not need treatment for their condition. Conclusion: Awareness about mental health among medical students is a topic that must be focused on to a greater degree, to protect the future generations of doctors and help each of them individually to overcome their mental health problems.